Quality of life among patients undergoing hemodialysis in Penang, Malaysia - Diana Laila Ramatillah; Syed Azhar Syed Sulaiman; Amer Hayat Khan; Ong Loke Meng (Wolters Kluwer Medknow Publications, 2017)
Background Quality of life is one of the parameters to check the improvement of hemodialysis treatment among hemodialysed patients. Those patients will be dealing with this treatment in long term if this treatment is the only way for them to replace their kidney function and this thing will affect their quality of life. Objective To evaluate the quality of life patients on hemodialysis using kidney disease quality of life-short term 24 (KDQoL-SF24) Malaysian Version. Materials and Methods Cohort observational study was conducted in this study. The study included 78 hemodialysed patients in HD center Penang, Malaysia. Results There were 9 components which had the lower of the mean and standard deviation (SD) than the standard form; work status (15.01 ± 35.57), cognitive function (75.66 ± 13.75), quality of life social interaction (76.32 ± 16.11), sleep (55.86 ± 15.30), social support (59.61 ± 22.08), patient satisfaction (43.24 ± 15.32), physical functioning (50.06 ± 42.81), general health (29.62 ± 25.56), and role emotional (54.27 ± 49.92). In this HD center, the group of patient's age who had the lower mean ± SD from the KDQoL-SF Manual Standard were the first and the sixth groups of patient's age (≤20 and 61-70). Conclusion The study conducted in HD center, Penang, Malaysia showed that the scoring of work status, cognitive function, quality of social interaction, sleep, social support, patient satisfaction, physical functioning, general health, and role emotional were low than standard form.